The feasibility of the earthscraper design concept - Morales Miranda, Carlos Arturo (Kansas State University, 2017)
Presently, the design basis for urban areas with a scarcity of surface space is the construction of skyscrapers. Skyscrapers, even with a lot of challenges, have been a great solution for the development of large urban areas since their introduction, per modern definition, in the early 1900’s (Kelley, 2010). This has allowed us to have a “reach a new height” type of mentality, with which the industry has been able to develop new construction ideas and concepts to improve, if not reinvent, those that have been used for nearly a century. The appreciation and application of new concepts will lead us into a progressive path to improve the overall designs within the industry. The concept of earthscrapers, best described as an underground skyscraper, is very intriguing but more than anything attractive to those in the industry. These new concepts will also bring a set of new challenges, with which solutions will arise. The concept of earthscrapers is a major game changer, with a design that offers several comparison and contrast points to skyscrapers. Some of the main focus points when discussing the approach of designing earthscrapers in comparison to skyscrapers are its space constraints, structure stability, and energy efficiency. Consequently, the paper will review the technical literature within the industry on these three subjects and evaluate their advantages and disadvantages. At the same time the paper will be reviewing the building systems of safety, mechanical, electrical and lighting applicable to this concept and discuss its challenges and effects on the overall design. Overall, this report covers and evaluates research done surrounding this design concept as well as providing topics and information that will need further testing and investigation. Initially, it covers further description of the two design solutions being discussed, skyscraper and earthscrapers, as well as its challenges and future development. The report will follow by an evaluation of the different ways that these designs provide a solution in regards to space scarcity in urban areas, as well as what each requires to be classified as an efficient design. Then, different engineering system implementations in these designs are introduced and a comparison is presented with the most up to date information available in the industry. All this with the purpose to give an idea of the differences in energy efficiency between designs as well as some of the social and psychological effects that these may have on the occupants and community. Finally, an overall evaluation is made in regards to the different benefits and challenges that approaching this new design concept faces, while also providing some recommendations on what could be done within the industry in order to make this possibility a reality.
Keywords: Underground; Earthscraper; Skyscraper; Innovative; Architecture; Engineering